PURIFICATION, CHARACTERIZATION AND EVALUATION OF BIOLOGICAL ACTIVITY OF MANNOPROTEIN PRODUCED FROM SACCHAROMYCES CEREVISIAE BY - H. GH. Rasheed; N. H. Haydar (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The current study was aimed to evaluate the biological activity of mannoprotein produce from local isolate S. cerevisiae BY. The results of purified mannoprotein using gel filtration chromatography revealed higher ratio of protein to mannose reached to 87.1%. FTIR indicated the presence of C-H and O-H bands could be due to the protein and carbohydrate components, respectively.C=N band due to acylated amino sugars frequently found in glycoproteins, HPLC indicated the presence of mannoprotein to 12 kinds of amino acid.Antibacterial, anti-adhesion and anti-biofilm activities of mannoprotein were evaluated against some pathogenic bacteria. Mannoprotein showed slightly inhibition zones ranged (10to14mm) and(9to 13mm) against P.aeruginosa and S.aureus respectively at concentration of mannoprotein from 50 to 200 mg/ml.The results showed higher anti-adhesive property of mannoprorein against P.aeruginosa (51.1%) and slightly antiadhesion againstS. aureus 19% at 200 mg / ml of mannoprotein. Results of the anti-biofilm activity rises as the concentration of mannoprotein increases and reached to 51.8% against P. aeruginosa while slightly anti biofilm (19.7%) against S. aureus, at concentration of 200 mg/ml. The synergistic effect of mannoprotein with some antibiotics was studied.The combination of mannoprotein and antibiotics (Tetracycline, Gentamycin, Ampicillin and Ciprofloxacin)(1:1) at concentration 1mg/ml were studied. Results showed enhancement 26, 29, 33 and 36% of inhibition zone against P. aeruginosa while, enhancement was 20, 33, 40, and 14 % for S. aureus, respectively. The results demonstrated that mannoprotein possess antimicrobial activity in nature. Hence if co-administrated with another inhibitory agent, the mixture reduces the survival of pathogens.